Improvement of sleep architecture in the follow up of a patient with bilateral paramedian thalamic stroke - Fonseca, Ana Catarina (2011)
Normal sleep architecture and arousal require an intact thalamus. Thalamic vascular lesions, particularly in the paramedian region may cause arousal disturbances and hypersomnolence. Although hypersomnolence is one of the main characteristics of acute bilateral paramedian thalamic infarcts, there are only scarce reports in literature concerning polysomnographic follow-up of these patients. The few reported cases in literature show that sleep stages do not significantly change from the acute to chronic phase. We present a case report of a patient with a bilateral paramedian thalamic infarct in which a polysomnographic evaluation of sleep was performed four days and five months after stroke. In the acute phase, polysomnography showed an impairment of phase 2 NREM and absence of phase 3 and 4 NREM with absent sleep spindles. After the acute stroke phase, hypersomnolence improved and sleep spindles reappeared as well as phase 3 and 4 of NREM sleep. Our patient clear clinical and polysomnographic improvement makes us suppose that in this case the initial impairment could have been essentially due to a functional transitory impairment of the thalamocortical and corticothalamic connections. This case report is peculiar because it discloses a marked improvement of sleep architecture which to the best of our knowledge has not been clearly described before.